1999
DOI: 10.1002/(sici)1098-2353(1999)12:5<326::aid-ca3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging and three-dimensional reconstructions of shoulders with anterior glenohumeral instability

Abstract: Glenohumeral instability is a common occurrence following anterior dislocation of the shoulder joint, particularly in young men. The bony abnormalities encountered in patients with glenohumeral instability can be difficult to detect with conventional radiography, even with special views. The aim of our study was to evaluate the bony abnormalities associated with glenohumeral instability using CT imaging with 3‐D reconstruction images. We scanned 11 patients with glenohumeral instability, one with bilateral sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 10 publications
0
29
1
1
Order By: Relevance
“…19 Other studies have confirmed the usefulness of CT scanning for evaluating the bony defects associated with glenohumeral instability. 20 Currently, precise en face 3D CT views are preferred for the evaluation of a glenoid bony defect. 15 However, 3D CT imaging has several disadvantages, including higher cost compared with standard X-ray imaging, the need for further magnetic resonance imaging evaluation for capsulolabral pathologies, and the relatively high radiation dose resulting from the CT exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Other studies have confirmed the usefulness of CT scanning for evaluating the bony defects associated with glenohumeral instability. 20 Currently, precise en face 3D CT views are preferred for the evaluation of a glenoid bony defect. 15 However, 3D CT imaging has several disadvantages, including higher cost compared with standard X-ray imaging, the need for further magnetic resonance imaging evaluation for capsulolabral pathologies, and the relatively high radiation dose resulting from the CT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, 3D CT imaging has several disadvantages, including higher cost compared with standard X-ray imaging, the need for further magnetic resonance imaging evaluation for capsulolabral pathologies, and the relatively high radiation dose resulting from the CT exposure. 20 Saito et al 18 reported that the mean orientation of the defect was pointing toward the 3:00 o'clock position of the glenoid and that these defects continued from the anterosuperior glenoid rim to the inferior glenoid rim. In our study, we evaluated the en face 3D CT view of the cadaveric glenoid and the glenoid of patients with instability, the length was standardized and compared with the bone defect, and the greatest size difference was detected at the 3:20 o'clock position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particolare, molti autori hanno riportato l'uso della tomografia computerizzata (TC) al fine di stabilire dimensioni, sede e tipo (frattura o erosione) del difetto glenoideo associato con l'instabilità gleno-omerale utilizzando ricostruzioni tridimensionali (3D) volume rendering technique (VRT) [15,[19][20][21][22][23], o bidimensionali (2D) multi-planar reconstruction (MPR) [14,[24][25][26][27]. La porzione mancante della glena misurata sulle acquisizioni TC può essere calcolata come percentuale dell'area della glena inferiore (metodo del cerchio) [15,19,24], o percentuale dell'ampiezza massima della glena [14,21,25,26].…”
Section: Comparison Between 2d and 3d Computed Tomography Evaluation unclassified
“…3,4,8,12,27,29,30,32 Laboratory and clinical studies have shown that these defects can influence the outcome of treatment for recurrent anterior glenohumeral instability and changes the biomechanics of the glenohumeral joint. 3,4,10,11,16,19,22,31,33 However, there is no consensus regarding the exact role of a glenoid defect in glenohumeral instability.…”
mentioning
confidence: 99%